2012
DOI: 10.1039/c1dt11521a
|View full text |Cite
|
Sign up to set email alerts
|

Solution behavior of iron(iii) and iron(ii) porphyrins in DMSO and reaction with superoxide. Effect of neighboring positive charge on thermodynamics, kinetics and nature of iron-(su)peroxo product

Abstract: The solution behavior of iron(III) and iron(II) complexes of 5(4),10(4),15(4),20(4)-tetra-tert-butyl-5,10,15,20-tetraphenylporphyrin (H(2)tBuTPP) and the reaction with superoxide (KO(2)) in DMSO have been studied in detail. Applying temperature and pressure dependent NMR studies, the thermodynamics of the low-spin/high-spin equilibrium between bis- and mono-DMSO Fe(II) forms have been quantified (K(DMSO) = 0.082 ± 0.002 at 298.2 K, ΔH° = +36 ± 1 kJ mol(-1), ΔS° = +101 ± 4 J K(-1) mol(-1), ΔV° = +16 ± 2 cm(3) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…Kinetic and equilibrium studies showed the reaction between the Fe(II) precursor and O À 2 to be fast, with the equilibrium strongly in favor of the bound species. New experimental and theoretical evidence suggests that 16 actually exists in equilibrium with its (η 1 -superoxo)Fe(II)(DMSO) isomer rather than a resonance form of 16 [45].…”
Section: Fe(iii)-superoxo Intermediatesmentioning
confidence: 97%
See 1 more Smart Citation
“…Kinetic and equilibrium studies showed the reaction between the Fe(II) precursor and O À 2 to be fast, with the equilibrium strongly in favor of the bound species. New experimental and theoretical evidence suggests that 16 actually exists in equilibrium with its (η 1 -superoxo)Fe(II)(DMSO) isomer rather than a resonance form of 16 [45].…”
Section: Fe(iii)-superoxo Intermediatesmentioning
confidence: 97%
“…Axial ligation at the heme center has also been demonstrated to have an effect on the binding mode of the peroxo bridge. In a recent example, addition of 1,5-dicyclohexylimidazole (DCHim) to compound 42 ( Figure 18) was shown to result in the fully end-on η 1 :η 1 coordination of the O 2 À 2 moiety to both metal centers (45), which was supported on the basis of rR, EXAFS, and UV-vis spectroscopy [131]. Values of ν(O-O) and ν(Fe-O) for 45 are similar to those observed for the η 2 :η 1 bound species.…”
Section: (μ-Peroxo)iron-copper Intermediatesmentioning
confidence: 98%
“…183 The addition of excess potassium superoxide to Fe II (tBuTPP) (tBuTPP = meso -tetrakis( p-tert -butylphenyl)porphyrinato 2− ) generated the peroxo species [Fe III (O 2 2− )(tBuTPP)] − . This process could be reversed by addition of a proton source, triflic acid (HOTf).…”
Section: Metal-oxygen Complexesmentioning
confidence: 99%
“…As it is much slower than the first reaction step, the second reaction step was observed only at higher concentrations of superoxide (≥2 mM), and the final spectrum is that of the (su)peroxo adduct with an absorption maximum at 440 nm. 4,23,45,46,48,49 From the concentration-dependent measurements ( Figure 7), the second-order rate constants for the first and the second reaction steps were found to be 18.6 ± 0.5 M −1 s −1 and 2.8 ± 0.1 M −1 s −1 , respectively. Strikingly, these reaction rates are four to five orders of magnitude lower than the corresponding reaction rates for other porphyrin complexes in conventional organic solvents.…”
Section: ■ Introductionmentioning
confidence: 99%